Goods Movement Arm Robot Based On Color Image Processing - Darson, Karitas; Ir. Abd. Rabi; Gumilang , Yandhika Surya Akbar (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2023)
The process of sending goods by humans can consider several factors, namely the weight of the goods, the  amount  of  goods,  the  length  of  the  trip  and  the  required  human  labor.  The  heavier  and  more  goods  or  the farther the distance that must be traveled, the more human power is needed to move the goods. In addition, the impossibility of human work for 24 hours is also a factor that affects the efficiency and quality of the operation. From these problems,  we need a robotic arm for moving goods based on image processing. Where in the early stages it starts with collecting color data on objects using a Raspberry Pi camera which will be processed by the Raspberry Pi 3b for data to be sent to Esp32 and will be forwarded to the servo control as a tool that drives the servo motor as the main mover on the robot arm.